Jesus and the Full Personhood of Women: Through the Lens of a Hermeneutics of Affect - Dreyer, Yolanda (Journal of early Christian history, 2018)
Biblical hermeneutics and New Testament exegesis have been based mostly on a rational approach and executed by means of cognitive methods. Feminist exegetes, female and male, who have pointed out the need for a hermeneutics of suspicion when exploring the wisdom, role and contribution of women in the Bible and have developed exegetical methods from this perspective, have also mostly done so by means of rational epistemologies. This article explores a "hermeneutics of affect" as an example of alternative "ways of knowing" to revisit some narratives on Jesus and women. A hermeneutics of affect is explained by making use of insights of Johann Gottfried Herder, Friedrich Schleiermacher and William James, whose epistemologies show an appreciation for affect and experience. From such a broadened rationality the article illustrates Jesus's disposition of respect for the full personhood of all people, including women.